Perencanaan Pembangunan Kabupaten Bengkalis Aspek Kebudayaan Melayu dalam Menopang Visi Provinsi Riau 2020 - Baskoro Wicaksono; Nur Meilani; Rury Febrina (Nakhoda: Jurnal Ilmu Pemerintahan, 2018)
Development planning is a must for every level of government, both central and regional, as mandated in Law No. 25 of 2004 concerning the development planning system. Bengkalis Regency as one of the regions in Riau Province also conducts development planning. The aspects of development planning in the Regency include Malay culture as a derivative of the Riau Vision 2020. Planning aspects of Malay culture development is a manifestation of the elected Regional Vision and Mission and can be seen in its harmony with the Province. The formulation of the problem in this study is how is the form of development planning aspects of Malay culture in Bengkalis District in supporting the Riau 2020 Vision? This study aims to describe the form of development planning aspects of Malay culture in Bengkalis Regency in supporting the Riau Vision 2020. The results of the study indicate that the planning of the development of the Malay cultural center has referred to the Provincial government planning documents, both contained in the RPJMD to RKPD even though they are only quantity, not yet fully touched the quality of the substance of Malay culture. The planning contained in the Bengkalis Regency RPJMD document is limited to the Vision and Mission statement, while the objectives to the strategic plan are not formulated. Nevertheless specifically in the Office of Culture, Youth and Sports expressly formulated this in the OPD Work Plan.